ENHANCING RURAL ECONOMIC PERFORMANCE THROUGH RURAL ELECTRIFICATION: A CASE STUDY OF ELECTRICITY COOPERATIVES IN LAGOS STATE - ADEBOSIN, GBADEBO WALID; SALAMI, LATEEF ABIODUN; ADESINA, AKINNIFESI; OJOMU, QUADRI TUNDE (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Electrification plays a crucial role in modern life and is central to sustainable development, particularly in rural areas of developing countries. Despite international and national commitments to achieving universal electricity access, progress has been slow, especially in sub-Saharan Africa, where few of rural populations have access to electricity. This study focuses on rural electrification in Lagos State, Nigeria, assessing the role of electric cooperatives in accelerating economic performance. Through a cross-sectional quantitative survey of rural households in two towns in Lagos State, the study investigates how rural electrification influences job and business creation, while addressing challenges such as infrastructure limitations and financial constraints. The findings indicate that while access to electricity has a marginal effect on job creation, government support emerges as a significant factor, positively impacting job opportunities. The study concludes that targeted government interventions, alongside addressing infrastructure bottlenecks, are critical for fostering sustainable job creation and economic development in rural electrification efforts